Complete mitochondrial genome of the fire goby, Nemateleotris magnifica (Perciformes, Gobiidae) - Sang-Eun Nam; Jae-Sung Rhee (Mitochondrial DNA. Part B. Resources, 2020)
In this study, we report on the complete mitochondrial genome of the fire goby, Nemateleotris magnifica (Perciformes, Gobiidae), a small attractive ornamental fish distributed in the Indo-Pacific region. The complete mitogenome of N. magnifica was 16,502 bp long and was typical of genus Nemateleotris mitogenomes in genomic content and structure, as the entire mitogenome contained 13 protein-coding genes (PCGs), 2 ribosomal RNA (rRNA) genes, 22 transfer RNA (tRNA) genes, and 1 control region. The phylogenetic analysis within gobiine-like and gobionelline-like gobiids based on the concatenated nucleotide sequences of the entire 13 PCGs confirmed the involvement in the gobiine-like group and the sister relationship with Nemateleotris decora. This mitogenome sequence will provide a useful resource for comparative analysis of the phylogenetic distance in gobiine-like gobiids.